Prevalence of bronchial asthma and correlation between the chemokine receptor 3 gene polymorphism and clinical asthma phenotypes among Egyptian asthmatic children - Magdy Mohamed Zedan; Mona El Wassefy; Eman Omar Khashaba; Hagar Sallam; Suzy Abd El Mabood (SpringerOpen, 2023)
Abstract Background Asthma is a chronic inflammatory airway disease characterized by episodic reversible airway obstruction that variably presents with cough, wheezing, shortness of breath, or chest tightness. It is a multigenetic disease, where both genetic and environmental factors have significant roles in pathogenesis. As regard asthma pathogenesis, the chemokine/chemokine receptor system is considered a key point of the immune response in most allergic diseases. This study was done to estimate the prevalence of bronchial asthma among school age children and explore the association between the underlying gene polymorphisms in chemokine receptor 3 (CCR3) and symptom-based clinical asthma phenotypes among a cohort of Egyptian children. Results Prevalence of asthma is increasing (20.6%). There are male asthma predominance. Family history of bronchial asthma and allergic diseases are predominant risk factors for asthma development. Sixty asthmatic cases with different clinical phenotypes were compared to 100 healthy controls, results explored that eosinophilic percent and total serum IgE are significantly higher among asthmatic cases versus controls. There are no significant difference regarding eosinophilic percent, serum IgE, and CCR3 T51C gene polymorphism among different clinical asthma phenotypes. There is no significant difference as regards degree of severity of asthma and level of asthma control between CCR3 T51C gene polymorphism. Conclusion We conclude the prevalence of bronchial asthma is increasing. Also, eosinophilic percent and serum IgE are elevated in asthma patients, while CCR3 T51C gene polymorphism frequency seemed to be more prevalent among asthmatic subjects however without statistical significance. We recommend a prospective study on larger sample size to validate our results.